Trajectories of depressive symptoms and risk of cardiovascular disease: Evidence from the China Health and Retirement Longitudinal Study. (January 2022) - Han, Longyang; Shen, Suwen; Wu, Yu; Zhong, Chongke; Zheng, Xiaowei
Abstract: Background: Previous studies have reported that depression is associated with higher risk of cardiovascular disease (CVD). However, the association between long-term depressive symptom patterns and the risk of CVD was not well characterized. Methods: A total of 8621 participants with three Center for Epidemiological Studies Depression Scale (CES-D) measurements from the China Health and Retirement Longitudinal Study were included. Trajectories of depressive symptoms were identified by latent mixture modeling. Cox proportional hazards regression models were used to examine the association of depressive symptom trajectories with CVD (stroke or cardiac events), and accounting for mortality as a competing risk for CVD. Results: We identified four distinct depressive symptoms trajectories, characterized by maintaining low CES-D score throughout the follow-up (no depressive symptoms; 5642 participants [65.44%]); high starting CES-D scores but then decreasing scores (decreasing depressive symptoms; 1329 participants [14.91%]); low starting CES-D scores then increasing scores (increasing depressive symptoms; 1154 participants [13.39%]) and maintained high CES-D scores throughout the follow-up (persistent depressive symptoms; 496 participants [6.26%]). During the follow-up period, 853 CVD events (including 362 strokes and 535 cardiac events) were recorded. Compared to participants in the no depressive symptom trajectory, those in the increasing depressive symptoms and persistent depressive symptom trajectories had an increased risk of CVD, with multiple-adjusted hazard ratios (95% confidence intervals) of 1.53 (1.28–1.82) and 1.68 (1.34–2.12), respectively. Individuals with increasing and persistent depressive symptoms trajectories also had higher risks of stroke and cardiac events. Conclusions: Individuals with increasing and persistent depressive symptom over time were associated with increased risk of incident CVD. Graphical abstract: Image 1 Highlights: This large-sample multicenter study examines the association between depressive symptoms patterns and risk of CVD. Increasing and persistent depressive symptoms trajectories were associated with higher risk of developing CVD. It is of clinical to use depressive symptoms trajectories as a screening method to identify individuals at risk of CVD.